PENERAPAN STRATEGI INDEX CARD MATCH PADA MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS X2 SMA TRI BHAKTI PEKANBARU - Ranti Octapiana Simanjuntak; Nahor Murani Hutapea; Suhermi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research based of the low result of students’ mathematics achievement in the class X2 SMA Tri Bhakti Pekanbaru. It can be seen from 32 students in the class, only 20 students who achieved the passing grade by the percentage 62,5% on the material Linear Equations and then the learning process still teacher center. The research is classroom action research. This aims research to increase learning process and students’ math achievement at class X2 SMA Tri Bhakti Pekanbaru through the implentation of the strategy index card match on cooperative learning model of STAD. The subject of the research are 32 students from class X2 SMA Tri Bhakti Pekanbaru, consist of 10 male and 22 famale students with the heterogenous level. Instrument to collect the data are observation and mathematics achivement test. The observation data analyzed by using descriptive and qualitative, and for students’ test by using descriptive and quantitative. The qualitative analysis showed an improvement of learning process prior to action to the first cycle and second cycle. The results of this research showed an increase in students achievement from the based-score with the percentage 62,5% to 68,75% on the first test and 84,375% on the second test. Based on the finding can be concluded the implentation of the strategy index card match on cooperative learning model of STAD to improve students’ mathematics achievement at class X2 SMA Tri Bhakti Pekanbaru in the second semester academic years 2014/2015.Key Word : Students’ Mathematics Achievement, Cooperative Learning Model STAD, Strategy Index Card Match, Classroom Action Research.